INNOVATION OF QUR’AN-HADITH TEACHERS IN IMPROVING LEARNING QUALITY AT MA PLUS RIYADLUL MUTA’ALLIMIN - Zuni Ulfah; Aniqoh Aniqoh (Jurnal Manajemen Pendidikan, 2026)
The development of digital technology has required teachers to implement innovative learning practices to enhance the quality of education, including in Qur’an-Hadith subjects at Islamic schools (madrasahs). This study aimed to describe the forms of innovation employed by Qur’an-Hadith teachers, analyze the implementation of these innovations in the learning process, and identify the supporting and inhibiting factors at MA Plus Riyadlul Muta’allimin. This research employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving Qur’an-Hadith teachers, the school principal, and students. Data were analyzed using the Miles, Huberman, and Saldaña model, which includes data condensation, data display, and conclusion drawing, while data trustworthiness was ensured through source, technique, and time triangulation. The findings revealed that learning innovations were implemented through the utilization of digital media and educational games, such as Canva, Quizizz/Wayground, Spin Wheel, educational snakes-and-ladders games, Smart TVs, and various active learning strategies. The implementation of these innovations was adjusted to students’ characteristics, learning materials, and classroom conditions, thereby increasing student participation, motivation, and engagement in learning activities. Supporting factors included teacher creativity, support from the school principal, and the availability of educational facilities, whereas inhibiting factors involved limited infrastructure and restricted internet access. The study concludes that the success of learning innovation is determined not only by the availability of facilities but also by teachers’ ability to creatively adapt and utilize existing resources.